Antibody-mediated thyroid dysfunction during T-cell checkpoint blockade in patients with non-small-cell lung cancer - Osorio, J.C.; Ni, A.; Chaft, J.E.; Pollina, R.; Kasler, M.K.; Stephens, D.; Rodriguez, C.; Cambridge, L.; Rizvi, H.; Wolchok, J.D.; Merghoub, T.; Rudin, C.M.; et al. (Annals of oncology, 2017)
Programmed cell death protein-1 (PD-1) blockade therapies have demonstrated durable responses and prolonged survival in a variety of malignancies. Treatment is generally well tolerated although immune-related adverse events (irAEs) can occur. Autoimmune thyroid dysfunction is among the most common irAE, but an assessment of the clinical, mechanistic, and immunologic features has not been previously described. Patients with advanced non-small-cell lung cancer (NSCLC) treated with pembrolizumab at Memorial Sloan Kettering Cancer Center (n=51) as part of KEYNOTE-001 (NCT01295827) were included. Thyroid function test and anti-thyroid antibodies were assessed prospectively at each study visit, beginning before the first treatment. Frequency of development of thyroid dysfunction, association with anti-thyroid antibodies, clinical course, and relationship with progression-free survival and overall survival to treatment with pembrolizumab was evaluated. Of 51 patients treated, 3 were hypothyroid and 48 were not at baseline. Ten of 48 [21%, 95% confidence interval (CI) 10% to 35%] patients developed thyroid dysfunction requiring thyroid replacement. Anti-thyroid antibodies were present in 8 of 10 patients who developed thyroid dysfunction, compared with 3 of 38 who did not (80% versus 8%,P<0.0001). Thyroid dysfunction occurred early (median, 42 days) in the pembrolizumab course, and a majority (6 of 10 patients) experienced brief, transient hyperthyroidism preceding the onset of hypothyroidism; no persistent hyperthyroidism occurred. Both hyperthyroidism and hypothyroidism were largely asymptomatic. Overall survival with pembrolizumab was significantly longer in subjects who developed thyroid dysfunction (hazard ratio, 0.29; 95% CI 0.09–0.94;P = 0.04). Thyroid dysfunction during pembrolizumab treatment of NSCLC is common and is characterized by early-onset, frequently preceded by transient hyperthyroidism, closely associated with anti-thyroid antibodies, and may be associated with improved outcomes. The presence of antibody-mediated toxicity in T-cell-directed therapy suggests an under-recognized impact of PD-1 biology in modulating humoral immunity.